Tibial tray debonding from the cement mantle is associated with deformation of the backside of polyethylene tibial inserts. (1st December 2021) - Bhalekar, Rohan M.; Nargol, Matthew E.; Shyam, Nish; Nargol, Antoni V. F.; Wells, Stephen R.; Collier, Ryan; Pabbruwe, Moreica; Joyce, Thomas J.; Langton, David J.
Abstract : Aims: The aim of this study was to investigate whether wear and backside deformation of polyethylene (PE) tibial inserts may influence the cement cover of tibial trays of explanted total knee arthroplasties (TKAs). Methods: At our retrieval centre, we measured changes in the wear and deformation of PE inserts using coordinate measuring machines and light microscopy. The amount of cement cover on the backside of tibial trays was quantified as a percentage of the total surface. The study involved data from the explanted fixed-bearing components of four widely used contemporary designs of TKA (Attune, NexGen, Press Fit Condylar (PFC), and Triathlon), revised for any indication, and we compared them with components that used previous generations of PE. Regression modelling was used to identify variables related to the amount of cement cover on the retrieved trays. Results: A total of 114 explanted fixed-bearing TKAs were examined. This included 76 used with contemporary PE inserts which were compared with 15 used with older generation PEs. The Attune and NexGen (central locking) trays were found to have significantly less cement cover than Triathlon and PFC trays (peripheral locking group) (p = 0.001). The median planicity values of the PE inserts used with central locking trays were significantly greater than of those with peripheral locking inserts (205 vs 85 microns; p < 0.001). Attune and NexGen inserts had a characteristic pattern of backside deformation, with the outer edges of the PE deviating inferiorly, leaving the PE margins as the primary areas of articulation. Conclusion: Explanted TKAs with central locking mechanisms were significantly more likely to debond from the cement mantle. The PE inserts of these designs showed characteristic patterns of deformation, which appeared to relate to the manufacturing process and may be exacerbated in vivo. This pattern of deformation was associated with PE wear occurring at the outer edges of the articulation, potentially increasing the frictional torque generated at this interface.